Cold spray for reducing venopuncture pain in hemodialysis patients; a randomized double-blinded controlled trial - Zahra Shafii; Neshiman Abdi Bastami; Amir Ahmad Nasiri (Journal of Nephropharmacology, 2020)
Introduction: The pain due to cannulation and needle insertion into blood vessels becomes problematic among patients suffering hemodialysis. Objectives: The present study aimed to assess the pain relieving effects of cooling sprays among patients undergoing hemodialysis. Patients and Methods: Eighty patients aged higher than 18 years who were on chronic hemodialysis were randomly assigned into two groups including the group received cooling spray for relieving pain (n = 40) and the group received stilled water as placebo (n = 40). In the intervention group and in a hemodialysis session, 2 puffs of the Cramer Cold Spray were sprayed 30 seconds before the cannulation. The pain severity was assessed by the visual analogue scale (VAS) method. Results: The mean of pain severity score was not different between the intervention and control group before intervention, however after intervention, the patients in the intervention group experienced milder pain due to cannulation as compared to control group (3.28 ± 1.13 versus 5.30 ± 1.76; P < 0.001). Interviewing with the patients receiving cooling spray showed willingness to the use of spray in 87.5% of cases. The local complication due to the use of cold spray was revealed only in 5% of patients. Conclusion: The use of cooling spray in hemodialysis patients can reduce the pain caused by needle insertion. This method can be routinely used as a non-pharmacological pain relief method to reduce pain in hemodialysis patients